The Protective and Therapeutic Function of Small Heat Shock Proteins in Neurological Diseases - Brownell, Sara E.; Becker, Rachel; Steinman, Lawrence (Frontiers in Immunology, 2012)
Historically, small heat shock proteins (sHSPs) have been extensively studied in the context of being intracellular molecular chaperones. However, recent studies looking at the role of sHSPs in neurological diseases have demonstrated a near universal upregulation of certain sHSPs in damaged and diseased brains. Initially, it was thought that sHSPs are pathological in these disease states because they are found in the areas of damage. However, transgenic overexpression and exogenous administration of sHSPs in various experimental disease paradigms have shown just the contrary – that sHSPs are protective, not pathological. This review examines small heat shock proteins in neurological diseases and highlight the potential of using these neuroprotective sHSPs as novel therapeutics. It will first address the endogenous expression of sHSPs in a variety of neurological disorders. Secondly, it will focus on recent studies that have investigated the therapeutic potential of small heat shock proteins. Finally, it will provide a model of what we think is the function of small heat shock proteins in neurological diseases.